Pendidikan Agama Islam Budi Pekerti Dan Penilaian Kurtilas (Studi Kasus Di SDN 2 Kaliwulu Kecamatan Plered Kabupaten Cirebon) - Abdul Khayi (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
This study describes the learning of Islamic education and the character and application of assessments based on the 2013 curriculum (kurtilas), this study is a case study in elementary school (SDN 2) Kaliwulu district Cirebon, the assessment instruments used are observation, self-assessment and assessment among peers, while in the cognitive domain there are three assessment instruments, namely written test, oral test and temporary assignment in the psychomotor domain, the assessment instrument used includes four, namely performance, product, project and portfolio. Data analysis is done by describing the data that has been collected by testing the validity of the data through triangulation. The application of kuirikulum using the scientific approach and the application of authentic assessment is expected to be the learning of Islamic religious education and character at SDN 02 to run optimally..Keyword: Islamic education, assessmen, curricularKajian ini mendiskripsikan pembelajaran pendidikan Islam dan budi pekerti dan penerapan penilaian berdasarkan kurikulum 2013 (kurtilas), kajian ini  adalah studi kasus di sekolah dasar (SDN 2) Kaliwulu kabupaten Cirebon, instrument penilaiannya yang digunakan  yaitu observasi, penilaian diri dan penilaian antar teman sejawat, sedangkan pada ranah kognitif terdapat tiga instrument penilain yaitu tes tulis, tes lisan dan penugasan sementara pada ranah psikomotorik instrument penilian yang digunakan meliputi empat yaitu performance, produk, proyek dan portofolio. Analisis data dilakukan dengan mendeskripsikan data yang telah dikumpulkan dengan uji keabsahan data melalui triangulasi. Penerapan kuirikulum dengan mengunakan pendekatan saintifik dan  penerapan penilaian autentik diharapkan pembelajaran pendidikan agama islam  dan budi pekerti di SDN 02 berjalan optimal.